National Police of Ukraine as a Party to a Police Service Contract - S. V. Vereitin (Law and Safety)
Scientific approaches to determining the legal status of the employer in labor relations have been studied considered. The author has studied the norms of the Law of Ukraine “On the National Police”, which determine the identity of the employer and his authority to enter into a police service contract.